2019
DOI: 10.3390/nu11020302
|View full text |Cite
|
Sign up to set email alerts
|

The Reasons for Doing Physical Exercise Mediate the Effect of Self-Esteem on Uncontrolled Eating Amongst Nursing Personnel

Abstract: Background: Since the beginning of the 20th century, the importance of creating healthy work environments and promoting the health of workers in the healthcare sector to create Healthy and Resilient Organizations has been emphasized. In this context, self-esteem is an essential construct which influences health and healthy life styles, and, therefore, the general wellbeing of nurses. The objective of this study was to analyze the mediating role of reasons for exercising in the effect that self-esteem has on un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The results of these studies have shown that poor sleep quality and the type of food consumed affect the self-esteem of nurses [ 31 ]. In other studies, using a group of 1094 nurses, it was found that global self-esteem had a direct and indirect effect on uncontrolled eating [ 32 ]. Abnormal eating behavior often signals problems with self-esteem, acceptance of one’s own body and difficulties with adaptation in the group [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies have shown that poor sleep quality and the type of food consumed affect the self-esteem of nurses [ 31 ]. In other studies, using a group of 1094 nurses, it was found that global self-esteem had a direct and indirect effect on uncontrolled eating [ 32 ]. Abnormal eating behavior often signals problems with self-esteem, acceptance of one’s own body and difficulties with adaptation in the group [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, self-esteem determines whether physical exercise is done to improve one's image, recognition or social affiliation. 55 In further research into the nurses' quality of life, it may be assumed that self-esteem as an individual's potential helps identify the strengths and weaknesses as regards the professional role. Proprietary study proved that a strong determinant which affects the perception of the quality of life is the professional burnout experienced by nurses as both physical and mental fatigue or exhaustion associated with the personal life sphere as well as with the work conditions and in contacts with patients.…”
Section: Discussionmentioning
confidence: 99%